2006
DOI: 10.1554/06-005.1
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Analyses of Admixture and Introgression Among Hybridizing Heliconius Butterflies

Abstract: Introgressive hybridization is an important evolutionary process and new analytical methods provide substantial power to detect and quantify it. In this study we use variation in the frequency of 657 AFLP fragments and DNA sequence variation from 15 genes to measure the extent of admixture and the direction of interspecific gene flow among three Heliconius butterfly species that diverged recently as a result of natural selection for Miillerian mimicry, and which continue to hybridize. Bayesian clustering based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 63 publications
(22 reference statements)
2
93
0
1
Order By: Relevance
“…Empirical studies that document genetically cryptic hybridization patterns are rare (James & Abbott, 2005;Keller, Fields, Berardi, & Taylor, 2014;Kronforst, Young, Blume, Gilbert, & McMillan, 2006;Lavretsky, Engilis, Eadie, & Peters, 2015;Mims, Darrin Hulsey, Fitzpatrick, & Todd Streelman, 2010), and strong inferences often require sampling of reference populations of parental species as well as cytoplasmic and nuclear markers. Reference populations are necessary because repeated recombination and backcrossing can homogenize nuclear genotypes, which makes it challenging to distinguish hybrid populations from subpopulations of parental species (Della Croce, Poole, & Luikart, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies that document genetically cryptic hybridization patterns are rare (James & Abbott, 2005;Keller, Fields, Berardi, & Taylor, 2014;Kronforst, Young, Blume, Gilbert, & McMillan, 2006;Lavretsky, Engilis, Eadie, & Peters, 2015;Mims, Darrin Hulsey, Fitzpatrick, & Todd Streelman, 2010), and strong inferences often require sampling of reference populations of parental species as well as cytoplasmic and nuclear markers. Reference populations are necessary because repeated recombination and backcrossing can homogenize nuclear genotypes, which makes it challenging to distinguish hybrid populations from subpopulations of parental species (Della Croce, Poole, & Luikart, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have assigned individuals to parental and hybrid categories using dominant markers have been based on a wide range of numbers of loci. For example, searches in the literature identified studies that have used as few as 4 loci (Gonzalez- Perez et al 2004) and as many as 657 loci (Kronforst et al 2006). While the number of loci necessary to successfully examine a given situation will vary based on factors such as the goals of the study, the resolution required, and the divergence levels of the hybridizing taxa, it is also likely that much of the variation in the numbers of markers used in previous studies is due at least in part to a lack of appropriate studies that aim to quantify the numbers of markers required under the different conditions found in specific cases.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, dominant markers, such as AFLP (Vos et al 1995) or RAPD loci (Welsh and McClelland 1990;Williams et al 1990) may be of interest, given that genotype data can be generated for such markers without any prior information about the genome. Indeed, a number of recent studies applied dominant markers to distinguish among parental and hybrid individuals in a wide variety of taxa, including plants (Wallace 2006;Magnussen and Hauser 2007;Liebst 2008;Milne and Abbott 2008;Gaskin et al 2009;Erfmeier et al 2011), birds (Haig et al 2004;Helbig et al 2005), barnacles (Tsang et al 2008), reptiles (Fitzpatrick et al 2008;Mebert 2008), amphibians (Yamazaki et al 2008), ticks (Araya-Anchetta et al 2013), butterflies (Kronforst et al 2006;Isaza et al 2012), and fishes (Young et al 2001;Huang et al 2005;Yamazaki et al 2005;Albert et al 2006;Oliveira et al 2006). These applications of dominant markers have occurred in spite of the fact that little quantitative assessment exists with which to evaluate the power of such markers in assigning individuals to various parental and hybrid categories.…”
Section: Introductionmentioning
confidence: 99%
“…To support the hypothesis of interspecific gene exchange, several studies [22,[83][84][85] have invoked as evidence of hybridization and introgression similar alleles shared among Heliconius species in gene genealogies of various nuclear protein-coding loci (mannose phosphate isomerase, triose phosphate isomerase, distalless, invected, white and scalloped). A limitation of these studies is that each compared variability among species only at one or a few geographical localities.…”
Section: Primer On Selection For Müllerian Mimicry Among Heliconius Smentioning
confidence: 99%
“…Brower [20] combined data for each of these genes in global analyses encompassing multiple geographical regions, and found that many of the 'introgressed' alleles are distributed widely among members of the H. cydno-H. melpomene clade from throughout their geographical ranges, a pattern explained at least as well by retention of ancestral polymorphism as by recent introgressive hybridization [86,87]. Thus, oft-cited claims of ongoing, evolutionarily significant gene flow between H. cydno and H. melpomene [83,84,88] should be viewed with circumspection (as suggested by Kronforst et al [89]). …”
Section: Primer On Selection For Müllerian Mimicry Among Heliconius Smentioning
confidence: 99%